Principles of the New Ecosystem Formation: economic aspects - Iakhiaev D. B., Voronina L. V., Grigorishchin A. V., Shiriaevskii D. S., Oshomkov T. A., Kopchenov A. A., Skliarenko R. P., Radina O. I., Malinina O. I., Kruglov V. N., Tiutin D. V., Chibilyova V. P., Korba O. A., Akoeva M. A., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Kretinina L. V., Zakharova A. N., Lavina T. A., Gritskevich T. I., Shmidt I. I., Zhuplei I. V., Zadvorneva E. P. (Principles of the New Ecosystem Formation: economic aspects, 2023)
the chapter presents the experience of programs and projects to support and develop entrepreneurial education, student entrepreneurship, including technological entrepreneurship, and the formation of business competencies among students in the system of the Russian educational space, identified based on the analysis of materials from federal innovation platforms of the Russian Federation.
Keywords: предпринимательское образование; entrepreneurial education; образовательные организации высшего образования; студенческое технологическое предпринимательство; student technological entrepreneurship; студенческое предпринимательство; инженерное предпринимательство; student entrepreneurship; engineering entrepreneurship; educational organizations of higher education